Existence, uniqueness, and localization of positive solutions to nonlocal problems of the Kirchhoff type via the global minimum principle of Ricceri - In Hyoun Kim; Yun-Ho Kim (AIMS Mathematics)
The purpose of this paper is to demonstrate the existence and uniqueness of positive solutions to fractional $ p $-Laplacian problems with discontinuous Kirchhoff-type functions. The crucial tools for getting these results are the uniqueness result of the Brézis–Oswald–type problem and the abstract global minimum principle. The primary features of this paper are the discontinuity of the Kirchhoff coefficient in $ [0, \infty) $ and the localization of solutions.